Pembinaan, Sarana Prasarana dan Motivasi Latihan Atlet Anggar di Kabupaten Kendal Tahun 2020 (Universitas Negeri Semarang, 2022)
The achievement of an achievement in sports activities is influenced by various supporting factors as well as several supporting factors. One of the crucial supporting factors that can affect the achievement motivation variable is maintenance, coaching and the main thing is facilities and infrastructure. This research was carried out with the aim of knowing the system of coaching, managing and procuring sports infrastructure on the achievement and motivation of fencing athletes in Kendal Regency in 2020. This research uses descriptive quantitative research methods. Data collection techniques used in this study were observation, questionnaires (questionnaires), interview, population and sample determination. The data analysis of this study used descriptive statistical tests to determine the category of each variable and simultaneously tested the hypothesis with SPSS 21. The results of the study prove that the variables of coaching and infrastructure have a significant effect on the motivation of fencing athletes in Kendal district. The athlete's motivation variable is only 13.85 from the maximum value of 20, this calculation is in the low category. The coaching variable can be 20.05 which is included in the very high category from the maximum value of 24. Furthermore, the infrastructure variable can affect the achievement variable on the athlete's achievement, affecting the achievement variable of 19.80 which is included in the high category of the maximum value of 24.